2022
DOI: 10.4102/sajhivmed.v23i1.1391
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance and associated factors among people living with HIV in the Middle East and North Africa region

Abstract: Background: Identifying coronavirus disease 2019 (COVID-19) vaccine acceptance and associated factors among people living with HIV (PLHIV) in the Middle East and North Africa region is important to meet the need for broad-scale vaccination against COVID-19.Objectives: To investigate the COVID-19 vaccine acceptance rate and factors among PLHIV in the Middle East and North Africa region.Method: An online cross-sectional survey was conducted among PLHIV currently living in Egypt, Tunisia and Saudi Arabia between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(57 reference statements)
0
6
1
Order By: Relevance
“…This finding is higher than a study conducted in 2021 in eight major cities in China, where only 57.2% of patients were willing to be vaccinated [ 10 ]. This number is also higher than the report from a study in the Middle East and North Africa between March and August 2021, which stated a vaccine acceptance rate of 64.6% among PLHIV [ 25 ]. The current study started in September 2021, several months after the initiation of the COVID-19 vaccination program for the general population in Indonesia.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is higher than a study conducted in 2021 in eight major cities in China, where only 57.2% of patients were willing to be vaccinated [ 10 ]. This number is also higher than the report from a study in the Middle East and North Africa between March and August 2021, which stated a vaccine acceptance rate of 64.6% among PLHIV [ 25 ]. The current study started in September 2021, several months after the initiation of the COVID-19 vaccination program for the general population in Indonesia.…”
Section: Discussionmentioning
confidence: 59%
“…However, the acceptance rate among PLHIV is considerably lower than the WHO target of 100%, in contrast to the rate for the general population (70%). Concerns about vaccine safety in PLHIV, particularly related to drugdrug interactions with ART medications, may contribute to this disparity [38,39]. Education and trust-building are crucial to increase vaccine acceptance among PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, 68.4% of the global population is willing to receive the COVID-19 vaccination (19), and the acceptance of the COVID-19 vaccine varied extensively among different countries, ranging from 54.85% in Russia to 88.62% in China (20). Among PLWH, studies in China (which included eight cities but not Shijiazhuang) (21) and in the Middle East and North Africa region (22) have shown that the proportion of people willing to receive the COVID-19 vaccination was 57.2 and 64.6%, respectively. Therefore, to achieve early herd immunization, it is important to understand people's willingness to receive the COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%